ANALISIS KINERJA SALURAN DRAINASE DESA LIANG KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Glen Boyke Rehatta; Semuel Uneputty; Selly Metekohy (Jurusan Teknik Sipil, 2022)
Liang Village is an area located in Salahutu District, Central Maluku Regency, Maluku Province. The increase in the population of the village of Liang led to rapid development, as well as causing an increase in the number of settlements. The conversion of land functions into settlements results in reduced water infiltration into the ground so that surface water runoff increases. In addition, an increase in population, housing also causes an increase in waste discharge, and has the potential to reduce water absorption and channel capacity. So it is feared that in the next few years the existing canal capacity will not be able to drain water. This study aims to analyze the existing canal capacity for the next 10 years. From the research results K1 & K2 channels meet the requirements because the channel's Planned Debit (Qr) < Existing Debit (QS). Channel K1 : Qr (0.61404 m3/sec) < Qs(2,14 m3/sec). Channel K2 Qr (1.176 m3/s) < Qs(1.48 m3/s). Channels K3 – K8 do not meet the requirements because the channel's Planned Debit (Qr) > Existing Debit (QS). Channel K3 : Qr (2.085 m3/s) .> Qs(1.63 m3/s). Channel K4 : Qr (1.6782 m3/s) .> Qs(1.63 m3/s). Channel K5 : Qr (1.7661 m3/s) .> Qs(0.60 m3/s). Channel K6 : Qr (1.2197 m3/s) .> Qs(0.61 m3/s). Channel K7 : Qr (1.5991 m3/s) .> Qs(0.82 m3/s). Channel K8 : Qr (1.8081 m3/s) .> Qs(1.20 m3/s).